ADVOKASI GIZI PADA KADER POSYANDU DI DESA ORO-ORO OMBO KEC MATAN BATU KOTA BATU - Santoso Budiarjo; Rudy Joegijantoro (Jurnal Ilmiah Kesehatan Media Husada, 2014)
Malnutrition in children under 5 years old in Indonesia is a common problem in our society , especially in rural areas . This is evidenced by the high prevalence of malnutrition among children under five are related to the high infant born with low weight . Coverage of exclusive breastfeeding 0-6 months in Kecamatan Batu only reached 26.1 % were categorized as low when compared to the target of 67 % . This is caused by a lack of public awareness about the importance of exclusive breastfeeding for 69.2 % and lack of socialization to the community KADARZI of 92.3 % and the need for cooperation between Puskesmas, cadres , PKK and cross- sector and citizens are well established in order to achieve the target program . In order to help overcome these problems it is necessary to be implemented at the village level cadres empowerment . Programmed activities include Survelians , Advocacy , Training and Extension